Factors That Affect Student Compliance In Implementing The Covid 19 Protocol During The Learning OfflineAt SMAN 2 Pujut Central Lombok - Teguh Achmalona Fajariawan; Tety Ripursari; Muhammad Amrullah; Suswinda Yulisutomo (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The emergence of the Covid 19 pandemic has changed various aspects including education. The strict covid-19 protocol must remain in place in the face of offline learning methods. The research method used is quantitative correlation with sectional cros approach. The sampling method using accidental sampling with a sample of 113 respondents. Data from the results of the study was then processed using logistic regression test. Statistical test results showed the understanding variable p value = 0.042, supervision p value = 0.003, punishment p value = 0.038. The results show that there is a significant influence between the level of understanding, supervision and punishment with the compliance of students in carrying out the covid 19 protocol in offline learning at SMAN 2 Pujut Central Lombok. Student compliance in implementing the covid 19 protocol in offline learning is influenced by the factors of understanding, supervision and punishment given to students.